2020
DOI: 10.1186/s12887-020-1978-5
|View full text |Cite
|
Sign up to set email alerts
|

The associations between some biological markers, obesity, and cardiovascular risk in Slovenian children and adolescents

Abstract: Introduction: The occurrence of cardiovascular diseases and metabolic disorders steadily increases with the body mass index (BMI). Since the latter is not the best and earliest indicator of obesity and cardiovascular risk, the aim of the study was to evaluate some potential biological markers that would allow us to detect children and adolescents at higher risk at an early stage. Methods: A sample of 330 children and adolescents were included in the study and divided into four groups: obese patients with hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…One of the crucial aims to prevent pediatric obesity complications is to detect children with higher cardiovascular risk and IR at an early stage [ 14 , 21 ]. Among clinical markers, BMI percentile and WC are frequently used in practice but with certain limitations [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the crucial aims to prevent pediatric obesity complications is to detect children with higher cardiovascular risk and IR at an early stage [ 14 , 21 ]. Among clinical markers, BMI percentile and WC are frequently used in practice but with certain limitations [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among clinical markers, BMI percentile and WC are frequently used in practice but with certain limitations [ 22 ]. Although BMI is used as a measure of obesity, it is not sensitive enough to detect early fat accumulation and early CVD risk [ 14 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the relationship between leptin and adiponectin, in spite of the many studies which have shown decreased levels of adiponectin and increased levels of leptin in children with obesity, their codependency is not well understood [85]. High leptin to adiponectin ratio is also a predictive value for obesity and an adverse metabolic profile in children that seems to be sex-specific [86].…”
Section: Altered Secretion Of Adipokinesmentioning
confidence: 99%
“…High leptin to adiponectin ratio is also a predictive value for obesity and an adverse metabolic profile in children that seems to be sex-specific [86]. Both adipokines, leptin and adiponectin, have been shown to be good biomarkers of future cardiometabolic risk, and have been found to be associated with adiposity biomarkers such as BMI and WHR, both in children and adolescents with obesity [85,86]. High leptin levels along with elevated circulating triglycerides in children with obesity are associated with BMI, WC and WHR [87].…”
Section: Altered Secretion Of Adipokinesmentioning
confidence: 99%